The carboxyl-terminal region of human coagulation factor X as a natural linker for fusion strategies. Issue 173 (January 2019) - Ferrarese, Mattia; Pignani, Silvia; Lombardi, Silvia; Balestra, Dario; Bernardi, Francesco; Pinotti, Mirko; Branchini, Alessio
Abstract: Fusion with human serum albumin (HSA), which represents a well-established technique to extend half-life of therapeutic proteins, commonly exploits intervening peptide linkers as key components. Here, we explored the human coagulation factor X (FX) carboxyl-terminal region, previously demonstrated by us to be dispensable for secretion and coagulant activity, as a natural linker for fusion purposes. To test our hypothesis, we compared direct FX-HSA fusion with the designed FX-HSA fusion proteins mimicking the recombinant activated factor VII (rFVIIa)-HSA or factor IX (FIX)-HSA chimeras, both strongly dependent from artificial linkers. Three constructs were produced by direct tandem fusion (FX-HSA) and through flexible (glycine/serine; FX-GS-HSA, mimicking rFVIIa-HSA) or cleavable (incorporating the FX activation site; FX-CL-HSA, mimicking FIX-HSA) linkers. The FX-HSA was efficiently secreted and displayed prolonged plasma persistence in mice. All chimeras possessed remarkable pro-coagulant activity, comparable to FX for FX-HSA (88.7 ± 6.0%) and FX-CL-HSA (98.0 ± 16.4%) or reduced for FX-GS-HSA (55.8 ± 5.4%). Upon incubation with activators, FX-HSA and FX-CL-HSA displayed a correct activation profile while the FX-GS-HSA activation was slightly defective. In fluorogenic-based assays, FX-HSA showed normal activity over time and a specific amidolytic activity (1.0 ± 0.12) comparable to that of FX. Overall, the FX-HSA features indicate that the FX carboxyl-terminal region represents an intrinsic sequence allowing direct tandem fusion. Our results provide the first experimental evidence for i) a coagulation factor fusion protein with biological properties independent from artificial linkers, ii) the suitability of FX carboxyl-terminal region as a natural linker for fusion purposes. Highlights: Direct tandem fusion of FX to albumin preserves coagulant activity. Direct tandem fusion of FX to albumin extends persistence in vivo . Efficacy of the direct FX-albumin fusion is independent from artificial linkers. The carboxyl-terminal region of FX may act as a natural linker for fusion strategies.